East and west of Zagros : travel, war and politics in Persia and Iraq 1913-1921 - Edmonds, C. J. (Iran Studies, 2010)
C.J. Edmonds published articles in orientalist journals and co-authored with Taufiq Wahby A Kurdish-English dictionary (Oxford, 1966). He published his memoirs of Iraq, Kurds, Turks, and Arabs : politics, travel and research in North-Eastern Iraq, 1919-1925 (London - New York, 1957), but his Persian memoirs remained unpublished. It tells how, after studying oriental languages in Cambridge, he became Consular Officer in Bushire, participated in British campaigns in Mesopotamia during First World War. As a Political Officer in Luristan Edmonds was in charge of the oil fields' security and was sent to Northern Persia after the war, a direct witness of the Jangal upheaval and the 1921 coup d'Etat.